Rethinking state-non-state alliances change and continuity in the U.S.-Kurdish relationship - Yesiltas, Ozum, 1979- (Kurdish societies, politics, and international relations., 2022)
"Rethinking State-Non-State Alliances explores how the Kurds' interactions with the U.S. transformed them into a considerable player in the Middle East while addressing how these transformations reshape the U.S. foreign policy. The book investigates the agency of non-state actors by putting the U.S.-Kurdish relationship within the broader International Relations context"--